2016
DOI: 10.1371/journal.pntd.0005180
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni Infection Can Jeopardize the Duration of Protective Levels of Antibody Responses to Immunizations against Hepatitis B and Tetanus Toxoid

Abstract: BackgroundSchistosomiasis is a disease of major public health importance in sub-Saharan Africa. Immunoregulation begins early in schistosome infection and is characterized by hyporesponsiveness to parasite and bystander antigens, suggesting that a schistosome infection at the time of immunization could negatively impact the induction of protective vaccine responses. This study examined whether having a Schistosoma mansoni infection at the time of immunization with hepatitis B and tetanus toxoid (TT) vaccines i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 75 publications
2
48
0
Order By: Relevance
“…The study provided an indication that the study subjects with chronic schistosomiasis were capable of responding to the vaccines and produced HPV specific IgG antibodies, however, after the 6 th week a decrease in IgG levels was observed. This reduced humoral response has also been observed in helminth infected subjects administered with a number of vaccines [22,[40][41][42].…”
Section: Chronic S Mansoni Infection Has No Significant Effect On Cymentioning
confidence: 57%
See 2 more Smart Citations
“…The study provided an indication that the study subjects with chronic schistosomiasis were capable of responding to the vaccines and produced HPV specific IgG antibodies, however, after the 6 th week a decrease in IgG levels was observed. This reduced humoral response has also been observed in helminth infected subjects administered with a number of vaccines [22,[40][41][42].…”
Section: Chronic S Mansoni Infection Has No Significant Effect On Cymentioning
confidence: 57%
“…Schistosomiasis, has been estimated to affect more than 250 million people with majority of cases occurring in Sub-Saharan Africa [18]. Several studies have shown that parasitic infections, especially schistosomiasis, impair long-term responses of certain vaccines such as BCG [19], TB [20], hepatitis B [21] and tetanus toxoid [22] that require a predominant Th1 response to be effective. During a chronic helminth infection, there is a characteristic induction of a Th2 response which down regulates Th1 responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1.75 mL of the heparinized blood was used to set up whole‐blood cultures for evaluation of in vitro production of cytokines (IL‐5, IL‐10, IL‐13, IFN‐γ) as previously described . Briefly, blood was diluted 1:5 in culture media (RPMI 1640, 1% L‐glutamine, 1% Penicillin‐streptomycin).…”
Section: Methodsmentioning
confidence: 99%
“…Reduced responses to vaccinations for tetanus toxoid (23), cholera (24), and BCG (25) have been associated with helminth coinfection, and children with malaria have been shown to mount weaker antibody responses to tetanus toxoid, Haemophilus influenzae, meningococcal polysaccharide, and Salmonella typhi vaccination (26) than uninfected children. While some parasitic infections do not affect the initial generation or levels of protective antibody, parasitic infections clearly affect the durability of these immune responses, as reported for HBV or tetanus toxoid vaccines in chronic schistosomiasis (27). Several mechanisms have been proposed for the antagonizing effects that coinfection has on vaccine durability.…”
Section: Coinfections: Vaccine Antagonistsmentioning
confidence: 98%